Multidrug resistance among Escherichia coli and Klebsiella pneumoniae carried in the gut of out-patients from pastoralist communities of Kasese district, Uganda - Stanley, Iramiot Jacob; Kajumbula, Henry; Bazira, Joel; Kansiime, Catherine; Rwego, Innocent B.; Asiimwe, Benon B. (PLoS ONE, 2018)
Introduction: Antimicrobial resistance is a worldwide public health emergency that requires urgent attention. Most of the effort to prevent this coming catastrophe is occurring in high income countries and we do not know the extent of the problem in low and middle-income countries, largely because of low laboratory capacity coupled with lack of effective surveillance systems. We aimed at establishing the magnitude of antimicrobial resistance among Escherichia coli and Klebsiella pneumoniae carried in the gut of out-patients from pastoralist communities of rural Western Uganda. Methods: A cross-sectional study was carried out among pastoralists living in and around the Queen Elizabeth Protected Area (QEPA). Stool samples were collected from individuals from pastoralist communities who presented to the health facilities with fever and/or diarrhea without malaria and delivered to the microbiology laboratory of College of Health Sciences-Makerere University for processing, culture and drug susceptibility testing. Results: A total of 300 participants fulfilling the inclusion criteria were recruited into the study. Three hundred stool samples were collected, with 209 yielding organisms of interest. Out of 209 stool samples that were positive, 181 (89%) grew E. coli, 23 (11%) grew K. pneumoniae and five grew Shigella. Generally, high antibiotic resistance patterns were detected among E coli and K. pneumoniae isolated. High resistance against cotrimoxazole 74%, ampicillin 67%, amoxicillin/clavulanate 37%, and ciprofloxacin 31% was observed among the E. coli. In K. pneumoniae, cotrimoxazole 68% and amoxicillin/clavulanate 46%, were the most resisted antimicrobials. Additionally, 57% and 82% of the E. coli and K. pneumoniae respectively were resistant to at least three classes of the antimicrobials tested. Resistance to carbapenems was not detected among K. pneumoniae and only 0.6% of the E. coli were resistant to carbapenems. Isolates producing ESBLs comprised 12% and 23% of E. coli and K. pneumoniae respectively. Conclusion: We demonstrated high antimicrobial resistance, including multidrug resistance, among E. coli and K. pneumoniae isolates from pastoralist out-patients. We recommend a One Health approach to establish the sources and drivers of this problem to inform public health.
Keywords: Multidrug resistance; Out-patients; Pastoralist communities; Antimicrobial resistance; Uganda